2006
DOI: 10.1111/j.1600-0420.2006.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Donor‐derived myofibroblasts in the ocular surface after allogeneic haematopoietic stem cell transplantation

Abstract: ABSTRACT.Purpose: To identify and characterize cells of donor origin in the ocular surface of female recipients who have undergone allogeneic haematopoietic stem cell transplantation (allo-SCT) from a male donor. Methods: Cytological impressions from the eyes of nine allografted patients (17 eyes) were analysed. Donor cells were identified using sex-chromosomespecific fluorescence in situ hybridization (FISH). Cells were characterized by immunohistochemistry (IHC) using the CK3 and CK19 epithelial markers, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…16 Donor-derived conjunctival epithelia and myofibroblasts have also been detected after sex-mismatched HSCT by staining for the Y chromosome in female allograft recipients. 17,18 However, the proportion of such cells is very small, and their contribution to pathogenic processes remains unknown.…”
Section: Basic Research On Ocular Cgvhdmentioning
confidence: 99%
“…16 Donor-derived conjunctival epithelia and myofibroblasts have also been detected after sex-mismatched HSCT by staining for the Y chromosome in female allograft recipients. 17,18 However, the proportion of such cells is very small, and their contribution to pathogenic processes remains unknown.…”
Section: Basic Research On Ocular Cgvhdmentioning
confidence: 99%
“…5,10,11 Briefly, samples were thawed and fixed in ethanol:acetic acid (3:1) for 15 min and then allowed to air dry. The membrane was removed from the plastic holder with a sterile scalpel and placed on a glass slide.…”
Section: Fluorescence In Situ Hybridization (Fish)mentioning
confidence: 99%
“…MFBs have been indicated as effector cells in various connective tissue disorders, and MFB dysregulation may cause fibrosis and loss of function. 3 In a previous study, 5 we utilized imprint cytology to extract cells from the ocular surface. We reported the presence of conjunctival donor-derived MFBs in allo-SCT recipients and also the occurrence of giant polyploid (PP) cells of recipient origin.…”
Section: Introductionmentioning
confidence: 99%
“…Our next aim seems be a reduction of the serious eye injuries among children caused by airsoft gun pellets. n a recent study (Hallberg et al 2006), our group reported the presence of donor-derived cells in the ocular surfaces of recipients of allogeneic bone marrow transplantation (allo-BMT). These cells were found to be myofibroblasts, i.e.…”
mentioning
confidence: 99%